2021
DOI: 10.1177/23094990211003349
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gluteus maximus tenotomy in primary total hip arthroplasty with posterior approach: Kinematic analysis of hip extensor strength

Abstract: Background: The posterior approach (PA) is the most commonly used surgical approach for total hip arthroplasty (THA), but the proximity of the sciatic nerve may increase the likelihood of sciatic nerve injury (SNI). Gluteus maximus tenotomy can be performed to prevent SNI because tenotomy increases the distance between the femoral neck and sciatic nerve and prevents compression of the sciatic nerve by the gluteus maximus tendon (GMT) during hip movements. We aimed to kinematically compare the postoperative hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It has also been suggested that damage to the hip extensor muscle group may occur with the PLA approach [ 11 , 12 ]. However, Imren et al found that there was no significant decrease in hip extension strength in patients who underwent total hip arthroplasty with PLA [ 22 ]. In this study, the isokinetic values ​​of both the operated and non-operated hips did not show a statistically significant difference between the PLA and ALA groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that damage to the hip extensor muscle group may occur with the PLA approach [ 11 , 12 ]. However, Imren et al found that there was no significant decrease in hip extension strength in patients who underwent total hip arthroplasty with PLA [ 22 ]. In this study, the isokinetic values ​​of both the operated and non-operated hips did not show a statistically significant difference between the PLA and ALA groups.…”
Section: Discussionmentioning
confidence: 99%
“…GMT releases with subsequent repair can be safely performed in primary total hip arthroplasty through the posterolateral approach, without any residual weakness to the hip extensors, to aid the surgeon in visualization and decrease the risk of SN injury 5,21 . Initially, patients may have difficulty climbing stairs or walking up an incline but that will resolve in almost all cases 21 .…”
Section: Treatmentmentioning
confidence: 99%
“…The deep gluteal space is bordered by the gluteus maximus posteriorly, the posterior acetabular column anteriorly, the gluteal tuberosity laterally, the sacrotuberous ligament medially, the inferior margin of the sciatic notch superiorly, and the ischial tuberosity inferiorly 5 . Because the SN lies medial and deep to the deep fibers of the gluteus maximus tendon (GMT) insertion on the gluteal tuberosity, the nerve can get compressed with hip flexion and internal rotation, between the ischial tuberosity and the GMT 5,21 . Furthermore, it resumes to travel through the posterior compartment of the thigh and innervates the muscles of the posterior thigh.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation